Regional organic matter and mineral dust are the main components of atmospheric aerosols over the Nam Co station on the central Tibetan Plateau in summer - Zhang, Haotian; Tian, Pengfei; Kang, Chenliang; Guo, Yumin; Yu, Zeren; Lu, Gefei; Tang, Chenguang; Du, Tao; Wang, Jiayun; Zhang, Zhida; Cao, Xianjie; Liang, Jiening; et al. (Frontiers in Environmental Science, 2022)
The transport of air pollutants from areas surrounding the Tibetan Plateau (TP) has recently been studied. however, the major sources of atmospheric total suspended particulate matter (TSP) on the central TP remain unclear due to a lack of in-situ observations on aerosol physico-chemical properties. Therefore, to quantitatively investigate the physico-chemical properties and reveal the major sources of atmospheric aerosols, a comprehensive field campaign was conducted at the site of Nam Co from August 6 to September 11, 2020. Aerosol loading was low during the campaign with average TSP mass concentration, scattering coefficient at 550 nm, and absorption coefficient at 670 nm being 10.11 ± 5.36 μg·m-3, 1.71 ± 1.36 Mm−1, and 0.26 ± 0.20 Mm−1, respectively. Organic matter (63.9%) and mineral dust (27.8%) accounted for most of the TSP mass concentrations. The average scattering Ångström exponent of 0.59 ± 0.14 reflected the influence of mineral dust, and the elemental fractions and the results of enrichment factor illustrated that crustal materials were the main contributors of mineral dust. The organic to elemental carbon ratio of 15.33 is probably caused by the aging that occurs during the transport of aerosols. The strong correlation between organic carbon and Ca2+ and the results of the electron microscopy analysis of single particles indicated that organic carbon and mineral dust had the same sources; however, the weak relation between mineral dust and wind speed indicated that local wind erosion was not the main contributor to the mineral dust. The potential source contribution function further illustrated that the summertime TSP in the central TP was mainly characterized by background biomass and mineral dust aerosols originating regionally from the ground within the TP.